KELAYAKAN PENDIRIAN USAHA ANGKUTAN UDARA NIAGA TIDAK BERJADWAL - Hidayat, Fajar; Tantri, Francis; Marlita, Devi (JURNAL MANAJEMEN TRANSPORTASI & LOGISTIK, 2016)
The aims of this Â study is Â to determine feasibility study of commercial air charter in PT. Sukses Mandiri Aviation. This research was conducted at PT. Sukses Mandiri Aviation, by using a qualitative descriptive research method to analyze marketing aspects of the market and financial feasibility studies. The result shows that PT. Sukses Mandiri Aviation has a captive market by cooperating with charter aircraft. Results of analysis of financial projections on the financial aspects of the feasibility study are: NPV is positive, the profitability is more than 1 (one), the IRR is greater than the interest, the payback period is less than the life of the investment,and financial ratios have met the requirements of the rules and regulations.